Przemieszczenia powłok obrotowych od wpływu temperatury - Jedraszak, B.; Baran, W.; Jankowiak, R. (Видавництво Національного університету «Львівська політехніка», 2007)
Problem of influence of stationary, non-symmetric field of temperature on deformations of thin-walled elastic shell of revolution is discussed in the paper. Analytical solution describing state of displacement for shell subjected to field of temperature is presented. The solution allowed to evaluate extremal values of components of vector of displacement for hyperboloidal cooling tower shell that can appear in a span of one day (i.e. on the 21-st of June).